2021
DOI: 10.3390/jcm10061171
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Bioptic Investigation of Patients with Primary Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is a chronic and heterogeneous disorder characterized by a wide spectrum of glandular and extra-glandular features. The hallmark of pSS is considered to be the immune-mediated involvement of the exocrine glands and B-cell hyperactivation. This leads pSS patients to an increased risk of developing lymphoproliferative diseases, and persistent (>2 months) major salivary gland enlargement is a well-known clinical sign of possible involvement by B cell lymphoma. Better stratifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
0
10
0
1
Order By: Relevance
“…An open surgical biopsy of the parotid gland is the recommended procedure in case of SG enlargement;19 20 however, the need of a skilled surgeon and the risk of potential complications limit its generalisability 20 21. Recently, ultrasound (US)-guided core needle biopsy (US-guided CNB) has been proposed as a diagnostic procedure for patients with pSS with suspected glandular lymphoma 17 22. However, evidence of this procedure’s safety, patient tolerance and standardisation remains limited 23.…”
Section: Introductionmentioning
confidence: 99%
“…An open surgical biopsy of the parotid gland is the recommended procedure in case of SG enlargement;19 20 however, the need of a skilled surgeon and the risk of potential complications limit its generalisability 20 21. Recently, ultrasound (US)-guided core needle biopsy (US-guided CNB) has been proposed as a diagnostic procedure for patients with pSS with suspected glandular lymphoma 17 22. However, evidence of this procedure’s safety, patient tolerance and standardisation remains limited 23.…”
Section: Introductionmentioning
confidence: 99%
“…In mice with an autoimmune background, lymphadenopathy occurs at 6 months, and B cells undergo monoclonal expansion, giving rise to lymphoma, by the age of 1 year 41 . Clinically, the presence of lymphadenopathy predicts future lymphoma risk, 42 and transcriptomic analysis has revealed CREM as a top upstream transcriptional regulator of molecular signatures associated with lymphomagenic transdifferentiation 43 . Furthermore, methotrexate and biologics reduce CREM expression (Figure 2A,F), and several cohort studies have reported protective effects of methotrexate and biologics on lymphoma 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…Die sonografischen Veränderungen der Speicheldrüsen haben dank der charakteristischen Darstellung mittlerweile einen hohen Stellenwert bei Diagnosestellung und Verlaufsbeurteilung von Autoimmunopathien wie dem Morbus Sjögren erlangt [33].…”
Section: Merkeunclassified